To solve the problem, let's define the variables:
- Let \( a \) be Tony's current age.
- Since Andrea is 6 years younger than Tony, her current age will be \( a - 6 \).
In two years:
- Tony's age will be \( a + 2 \).
- Andrea's age will be \( (a - 6) + 2 = a - 4 \).
According to the problem, in two years, Tony's age will be three times Andrea's age. This gives us the equation:
\[ a + 2 = 3(a - 4) \]
Now let's examine the provided options to find which one matches our derived equation:
- \( 3(a + 2) = a - 6 + 2 \) simplifies to \( 3a + 6 = a - 4 \) (Not correct).
- \( a + 2 = 3(a + 6 + 2) \) does not match our equation (Not correct).
- \( a = 3(a + 2) \) simplifies to \( a = 3a + 6 \) (Not correct).
- \( a + 2 = 3(a - 6 + 2) \) simplifies to \( a + 2 = 3(a - 4) \), which matches our derived equation.
Therefore, the correct option is:
\( a + 2 = 3(a - 6 + 2) \).